2011
DOI: 10.1038/srep00127
|View full text |Cite
|
Sign up to set email alerts
|

An N-methyl-d-aspartate receptor agonist facilitates sleep-independent synaptic plasticity associated with working memory capacity enhancement

Abstract: Working memory (WM) capacity improvement is impacted by sleep, and possibly by N-methyl-D-aspartate (NMDA) agonists such as D-cycloserine (DCS), which also affects procedural skill performance. However, the mechanisms behind these relationships are not well understood. In order to investigate the neural basis underlying relationships between WM skill learning and sleep, DCS, and both sleep and DCS together, we evaluated training-retest performances in the n-back task among healthy subjects who were given eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
2
8
0
Order By: Relevance
“…after sleep for emotional and neutral pictures, which might reflect that sleep-associated consolidation of these memories is not primarily a consequence of hippocampal reactivation (Debas et al, 2010;Diekelmann and Born, 2010;Karni et al, 1998;Wagner et al, 2001 but see also Albouy et al, 2008). The findings concur with previous studies that likewise failed to observe DCS-induced changes in overnight gains in cognitive skill, although benefits in retention occurred for working memory training and emotional memories when participants were awake (Kalisch et al, 2009;Kuriyama et al, 2011b). Interestingly, in a previous study of ours both blocking of NMDA receptors and of AMPA receptors impaired sleep-dependent gains in a procedural visual texture discrimination task (Gais et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…after sleep for emotional and neutral pictures, which might reflect that sleep-associated consolidation of these memories is not primarily a consequence of hippocampal reactivation (Debas et al, 2010;Diekelmann and Born, 2010;Karni et al, 1998;Wagner et al, 2001 but see also Albouy et al, 2008). The findings concur with previous studies that likewise failed to observe DCS-induced changes in overnight gains in cognitive skill, although benefits in retention occurred for working memory training and emotional memories when participants were awake (Kalisch et al, 2009;Kuriyama et al, 2011b). Interestingly, in a previous study of ours both blocking of NMDA receptors and of AMPA receptors impaired sleep-dependent gains in a procedural visual texture discrimination task (Gais et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…The concept of WM refers to the temporary storage and manipulation of information. Previous investigations suggest improvements of executive aspects of WM performance, for instance in monitoring and manipulation of information held online, by training [21] as well as positive effects of night-time sleep [22] , [23] . Moreover, we recently observed increased WM performance during a multiple nap compared to sleep deprivation protocol, specifically driven by heterozygous carriers of the ADA polymorphism [17] .…”
Section: Introductionmentioning
confidence: 98%
“…Contrary to Goshen et al the animals we used for our study were not raised in reverse cycle, and we thus performed all our behavioural studies during their less active period. Interestingly, several studies have demonstrated the influence of sleep and time of day on hippocampal-dependent plasticity and subsequent behavioural abilities [34], [35], [36], [37]. In addition, a recent paper revealed that, under physiological conditions, time of day influenced IL-1β and IL-1RI expression and speculated that IL-1 may contribute to the basal functioning of the suprachiasmatic nucleus (SNC) clock [38].…”
Section: Discussionmentioning
confidence: 99%